2020
DOI: 10.1136/bmjopen-2019-034136
|View full text |Cite
|
Sign up to set email alerts
|

Exposure to traffic-related particle matter and effects on lung function and potential interactions in a cross-sectional analysis of a cohort study in west Sweden

Abstract: ObjectivesTo investigate the long-term effects of source-specific particle matter (PM) on lung function, effects of Surfactant Protein A (SP-A) and glutathione S-transferase (GST) genes GSTP1 and GSTT1 gene variants and effect modification by single-nucleotide polymorphism (SNP) genotype.DesignCohort study with address-based annual PM exposure assigned from annual estimates of size (PM10, PM2.5 and PMBC) and source-specific (traffic, industry, marine traffic and wood burning) dispersion modelling.SettingGothen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
4
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
2

Relationship

4
5

Authors

Journals

citations
Cited by 10 publications
(5 citation statements)
references
References 43 publications
1
4
0
Order By: Relevance
“…PM 2.5 was available for only some parts of the study period, so we refrained from adjusting for this in our models. Finding mainly effects of PM 10 from tra c has been reported in other studies of speci c PM sources, where long-term exposure to particles from marine tra c or residential heating were not associated with respiratory health (33). However, when studying health effects of long-term exposure to air pollution, it is not unproblematic to disentangle resuspension and direct tra c exposure in dispersion models as these are highly correlated, giving extra importance to short-term studies with thorough source assignment.…”
Section: Tra C and Local Resuspensionsupporting
confidence: 69%
“…PM 2.5 was available for only some parts of the study period, so we refrained from adjusting for this in our models. Finding mainly effects of PM 10 from tra c has been reported in other studies of speci c PM sources, where long-term exposure to particles from marine tra c or residential heating were not associated with respiratory health (33). However, when studying health effects of long-term exposure to air pollution, it is not unproblematic to disentangle resuspension and direct tra c exposure in dispersion models as these are highly correlated, giving extra importance to short-term studies with thorough source assignment.…”
Section: Tra C and Local Resuspensionsupporting
confidence: 69%
“…Other studies have reported increased emergency visits due to asthma and COPD [36] and increased asthma and COPD mortality [37,38] after acute exposure to airway pollution. The pathophysiological changes due to particulate matters are not clarified, but genetic modification has been suggested [39].…”
Section: Discussionmentioning
confidence: 99%
“…Four SFTPA1 SNPs were genotyped and used, and three SFTPA2 SNPs were genotyped successfully and used (one assay failed). These SNPs are the same as are previously reported from the same cohort [ 30 ]. For NOS2 and NOS3 we did broader tagging SNP genotyping (including also obviously known candidate SNPs) across the genes to capture LD and haplotype variation.…”
Section: Methodsmentioning
confidence: 98%